Evaluation of innovative management of small fiberglass shipbuilding organisations in Croatia - Zanze, Josip (Oeconomica Jadertina, 2020)
The aim of this paper is to investigate the relationship between innovative management and four selected elements of the organization: longevity of the organisation, number of employees, level of education and seniority of employees of small fiberglass shipbuilding organisations in Croatia (SFSC). Innovative management, or innovation management by managers of organisations at all levels is a matter of survival of every organisation. This paper investigates the relationship between innovative management and the elements of the organisation, through the correlation of innovative management with six variables and 36 indicators and selected four organisation elements with four variables and 35 indicators. The above was investigated by a survey on the example of 11 selected SFSC organisations. The research started with the question what the correlation of this connection was. The statistical methods of the program Statistica 12 and SPSS 22 were used for the analysis of correlations. The results of the work in the used analysis led to a unique conclusion that there is no significant connection between innovative management and the selected four organisation elements.
Keywords: innovation; innovative management; elements of organisation; small shipbuilding